M-Changa : leveraging Kenya's mobile money market for community fundraising - Markovich, Sarit, (SAGE knowledge. Cases., 2016)
M-Changa was one of the fastest-growing fundraising platforms in Kenya, allowing Kenyans to use text messages on their mobile phones to send, receive, and track donated funds as well as solicit donations from family and friends. The young cofounders, Kyai Mullei and David Mark, had grown the company quickly by leveraging partnerships with large banks, mobile money operators, and NGOs. By April 2015, M-Changa had a team of five people serving 25,000 users. Now, it stood at a crossroads. M-Changa's board members had expressed concern that its multitude of partnerships may have spread the company too thin. The board urged Mullei and Mark to focus on the partnerships that would reap the most value for the company in the long run. This case study asks if M-Changa pursue partnerships?